The impact of the spacer and metal layer on the absorption of the heterostructures composed of TMDCs to design narrowband and broadband absorbers - Ansari, Narges; Mohebbi, Ensyieh; Rezaei, Narges (Optical and quantum electronics, 2023)
Owing to their exceptional optical and electronic properties, the two-dimensional transition metal dichalcogenide (TMDC) monolayers have received a great deal of attention. In fact, it has been suggested that heterostructures including spacers, metals, and two of the TMDC monolayers increase absorption of the narrowband and broadband in the visible range. This study investigates the effects of the number, place, and thickness of the spacers; metal thickness; and angle and polarization of the incident light on the absorption. Inserting the spacer into the structure increases the absorption via inducing light localization and enhancing the intensity of the light in the TMDC monolayers. Further, the effect of employing one spacer on improving the absorption is almost equal to making use of double spacers. The proposed structures by enhanced light-material interaction can raise the amount of the absorption over 90% throughout the broadband wavelength range of 300–480 nm and above 65% at the narrowband wavelength of 617 nm. The findings of the study suggest promising prospects of these structures for a variety of applications particularly in narrowband and broadband optical devices.